New music therapy faculty and the pursuit of fulfillment, success, and identity: A collective autoethnography. (July 2021) - Potvin, Noah; Belt, Courtney; Moore, Carolyn
Highlights: New music therapy faculty members face challenges transitioning to higher education. Collective autoethnography weaves multiple narratives into an integrative story. Success, fulfillment, and identity represented aspirational growth for new faculty. Unclear expectations and limited mentorship were challenges for achieving growth. Development of best practices for training and mentoring educators is needed. Abstract: Little is known about best practices for effectively developing and mentoring new music therapy faculty as they transition to the complex ecology of higher education. To address this gap, three new music therapy faculty explored their lived experiences as participant-researchers in a collective autoethnography designed to synthesize their perspectives into a shared, comprehensive story. Over the 2017–2018 academic year, data were collected from personal journals and focus groups interweaving individual and collective narratives and qualitatively analyzed via restorying, domain and taxonomic analysis, and inductive semantic thematic analysis. Forty-two total domains, or cultural categories, were identified and then consolidated into six primary themes: student relations, evaluation, self-preservation, competence, challenges, and colleague relations. Primary themes were further distilled into three composite themes – fulfillment, success, and identity—that participant-researchers experienced as aspirational goals that were critical for professional development yet difficult to conceptualize and achieve. The narrative stage of rising action reflected participant-researchers' aspirations to feel fulfilled, achieve success, and develop identity while contending with limited insight, guidance or direction. The findings provide foundational knowledge for future scholarship examining best practices for training and mentoring new faculty.